Hamlet à l’épreuve des librettistes - Francis Guinle (Revue LISA)
An opera libretto cannot be expected to reproduce the exact text of the literary or dramatic work on which it is based. The so-called “weaknesses” of the libretti may be accounted for by the fact that they are meant to be set to music. In some rare cases, where the libretto uses part of the original text (like Francis Poulenc’s Dialogues des Carmélites), the music closely follows the shape of the words, but usually it fulfills a poetical aspect lacking in the text. This seems particularly true when we consider 19th century opera. This implies that it is impossible to deal with the libretti without taking the music into account. In the case of Hamlet, what is the librettists’ approach? Where is Shakespeare’s tragedy to be found in Ambroise Thomas’s opera? What light does the opera shed on the reception of Shakespeare in the 19th century? These are the questions this article tries to answer.